Reproductive and genotoxic effects in zebrafish after chronic exposure to methyl methanesulfonate in a multigeneration study - Faßbender, Christopher (Ecotoxicology (London, England), 2013)
There is still controversy whether adverse effects by genotoxic anthropogenic pollutants are linked to the decline of fish populations. Further investigations into the relationship between genotoxic stress and detrimental effects on development and reproduction in fish are required. For this end, zebrafish (F0 generation) were exposed in vivo to the alkylating model genotoxin methyl methanesulfonate (MMS) from fertilization to the age of 1 year. F0 fish were mated over 6 months to check for reproductive capacities. F1 fish grew up without exposure in order to allow for regeneration. Mortality of F0 fish depended on MMS concentrations. In MMS-exposed F0 fish, times of first spawning were delayed and fertility was reduced. Using the alkaline comet assay and the micronucleus test, significant genotoxic effects were found in the livers, gills and gonads of either sex in the F0 generation. No detrimental effects on growth were found. In F1 fish with parental exposure, teratogenic effects were increased, and larval survival was reduced. However, fertility capacities of the non-exposed F1 generation had recovered. Development and survival rates further recovered in the F2 generation. Anthropogenic genotoxicants may thus play a considerable role in the decline of wild fish populations